Pengaruh Keadilan Pajak, Sistem Perpajakan, Dan Pemeriksaan Pajak Terhadap Persepsi Wajib Pajak Mengenai Penggelapan Pajak - Muhammad Zainuri Wicaksono; Umaimah Umaimah (Liquidity, 2025)
This study aims to observe each independent variable that has been determined in this study on taxpayer perceptions of tax evasion. Tax evasion is classified as a fatal problem that can disrupt state revenues. Taxpayers' assumptions about the effectiveness and fairness of tax forms are also vulnerable to tax audits believed to impact their potential to act to evade taxes. This discussion is quantitative in the form of a survey method involving some individuals and agencies in a region. For the report, multiple linear regression analysis was carried out to observe the contribution of each variable. The results of the study show that each independent variable contributes to taxpayer perceptions of tax evasion. These results indicate that improving the perception of fairness, simplifying the system, and strengthening audits can serve as effective strategies to reduce tax evasion practices.